Gestational Diabetes Mellitus and Iron Deficiency Anemia - Neslihan Yerebasmaz; Şeyma Asiltürk; Erdem Fadıllıoğlu; Özlem Şengül; Serdar Yalvaç; Ömer Kandemir (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To determine whether gestational diabetes mellitus is influenced by the presence of iron deficiency anemia in early pregnancy.